2019
DOI: 10.1093/phe/phz002
|View full text |Cite
|
Sign up to set email alerts
|

Adding Lithium to Drinking Water for Suicide Prevention—The Ethics

Abstract: Recent observations associate naturally occurring trace levels of Lithium in ground water with significantly lower suicide rates. It has been suggested that adding trace Lithium to drinking water could be a safe and effective way to reduce suicide. This article discusses the many ethical implications of such population-wide Lithium medication. It compares this policy to more targeted solutions that introduce trace amounts of Lithium to groups at higher risk of suicide or lower risk of adverse effects. The ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…Discussion is also ongoing on the beneficial (or not) effect of low intakes of Li-especially from potable (tap) water, that is basically a weak source of Li in the daily diet [23,30]. Nevertheless, in recent times, it has been added to mineral water [34]. Typically, foods such as various meats, dairy products, seafood, eggs and vegetables contain Li in low concentrations, e.g., the daily dietary intake in Jerzy Falandysz is visiting professor at affiliation 2.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion is also ongoing on the beneficial (or not) effect of low intakes of Li-especially from potable (tap) water, that is basically a weak source of Li in the daily diet [23,30]. Nevertheless, in recent times, it has been added to mineral water [34]. Typically, foods such as various meats, dairy products, seafood, eggs and vegetables contain Li in low concentrations, e.g., the daily dietary intake in Jerzy Falandysz is visiting professor at affiliation 2.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Li 2 CO 3 has been found to be poisonous above the maximal therapeutic dose (10.4 mg L −1 in blood) (Timmer and Sands, 1999 ). The debate on the relationship between increasing intakes of Li from municipal drinking water and a decrease in suicide rates (Marshall, 2015 ; Memon et al 2020 ) continues, an approach that has been suggested but also questioned (Gillman, 2019 ; Ng et al 2019 ; Szklarska and Rzymski, 2019 ). The active lithiation of foods and drinking water is highlighted as an area of current research aiming to increase the state of knowledge in this field (Szklarska and Rzymski, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microdoses of Li intake through drinking water may have antisuicidal, mood-stabilizing, antidepressive and antimanic effects. Moreover, the dietary Li was found to have a beneficial role in the prevention of dementia and Alzheimer’s diseases [ 2 , 6 , 7 ]. However, the biochemical mechanisms are still unelucidated.…”
Section: Introductionmentioning
confidence: 99%